Multi-lepton signatures of vector-like leptons with flavor - Stefan Bißmann; Gudrun Hiller; Clara Hormigos-Feliu; Daniel F. Litim (European Physical Journal C: Particles and Fields, 2021)
Abstract We investigate collider signatures of standard model extensions featuring vector-like leptons and a flavorful scalar sector. Such a framework arises naturally within asymptotically safe model building, which tames the UV behavior of the standard model towards the Planck scale and beyond. We focus on values of Yukawa couplings and masses which allow to explain the present data on the muon and electron anomalous magnetic moments. Using a CMS search based on $$77.4 \, \text {fb}^{-1}$$ 77.4 fb - 1 at the $$\sqrt{s}=13$$ s = 13  TeV LHC we find that flavorful vector-like leptons are excluded for masses below around 300 GeV if they are singlets under $$SU(2)_L$$ S U ( 2 ) L , and around 800 GeV if they are doublets. Exploiting the flavor-violating-like decays of the scalars, we design novel null test observables based on opposite sign opposite flavor invariant masses. These multi-lepton distributions allow to signal new physics and to extract mass hierarchies in reach of near-future searches at the LHC and the HL-LHC.